Effect of Control on the Mathematical Model of Hepatitis B Virus with Infective Migrant - , Folahan S. Akinboro, T. O. Oluyo, O. O. Kehinde, S. Alao (Archives of Current Research International, 2020)
The transmission dynamics of Hepatitis B Virus in a population with infective immigrant is presented with the inclusion of an optimal control strategy to curtail the spread of the virus. To understand the spread of this infection, we develop a mathematical model with control variables of migrant screening and public sensitization. The optimality system is characterized using Pontryagin’s maximum principle and solve numerically with an implicit finite difference method. Result of the numerical simulation is presented to illustrate the feasibility of this control strategy. The analysis reveals that combination of both control variables could be the most fruitful way to reduce the incidence of Hepatitis B virus.